Early-life exposure to indoor air pollution or tobacco smoke and lower respiratory tract illness and wheezing in African infants: a longitudinal birth cohort study. Issue 8 (November 2017) - Vanker, Aneesa; Barnett, Whitney; Workman, Lesley; Nduru, Polite M; Sly, Peter D; Gie, Robert P; Zar, Heather J
Summary: Background: Indoor air pollution (IAP) and environmental tobacco smoke (ETS) are associated with lower respiratory tract illness (LRTI) or wheezing in children. However, the effect of the timing of these exposures, specifically antenatal versus postnatal, and of alternate fuel sources such as the increasingly used volatile organic compounds have not been well studied. We longitudinally investigated the effect of antenatal or postnatal IAP and ETS on LRTI or wheezing prevalence and severity in African infants. Methods: Mother and infant pairs enrolled over a 3-year period in a birth cohort study in two centres in Paarl, South Africa, were followed for the first year of life for LRTI or wheezing illness. We measured exposure to IAP (particulate matter, nitrogen dioxide, sulphur dioxide, carbon monoxide, and volatile organic compounds benzene and toluene) using devices placed in homes, antenatally and postnatally. We measured ETS longitudinally by maternal self-report and by urine cotinine measures. Study staff trained in recognition of LRTI or wheeze documented all episodes, which were categorised according to WHO case definition criteria. We used multivariate logistic and Poisson regressions to explore associations. Findings: Between March 1, 2012, and March 31, 2015, we enrolled 1137 mothers with 1143 livebirths. Of 1065 infants who attended at least one study visit, 524 episodes of LRTI occurred after discharge with a wheezing prevalence of 0·23 (95% CI 0·21–0·26) episodes per child year. Exposures associated with LRTI were antenatal maternal smoking (incidence rate ratio 1·62, 95% CI 1·14–2·30; p=0·004) or particulate matter (1·43, 1·06–1·95; p=0·008). Subanalyses of LRTI requiring hospitalisation (n=137) and supplemental oxygen (n=69) found antenatal toluene significantly increased the risk of LRTI-associated hospitalisation (odds ratio 5·13, 95% CI 1·43–18·36; p=0·012) and need for supplemental oxygen (13·21, 1·96–89·16; p=0·008). Wheezing illness was associated with both antenatal (incidence rate ratio 2·09, 95% CI 1·54–2·84; p<0·0001) and postnatal (1·27, 95% CI 1·03–1·56; p=0·024) maternal smoking. Antenatally, wheezing was associated with maternal passive smoke exposure (1·70, 1·25–2·31; p=0·001) and, postnatally, with any household member smoking (1·55, 1·17 −2·06; p=0·002). Interpretation: Antenatal exposures were the predominant risk factors associated with LRTI or wheezing illness. Toluene was a novel exposure associated with severe LRTI. Urgent and effective interventions focusing on antenatal environmental factors are required, including smoking cessation programmes targeting women of childbearing age pre-conception and pregnant women. Funding: Bill & Melinda Gates Foundation, Discovery Foundation, South African Thoracic Society AstraZeneca Respiratory Fellowship, Medical Research Council South Africa, National Research Foundation South Africa, and CIDRI Clinical Fellowship.